Peningkatan Kompetensi Guru SMK Melalui Pelatihan Software Engineering - Fivia Eliza; Asnil Asnil; Irma Husnaini (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
Teacher competence must be increase by carried out continuously, because the success of learning is the responsibility of educators. Technology-based learning will help educators in the Industrial Revolution 4.0 era, especially vocational teachers who teach in the productive field (engineering subjects). The problem faced is the inability of teachers to use computers as learning media. The teacher has not been able to utilize software engineering that will help in the process of practical learning, such as NI Multisim and Proteus software in learning electrical circuits and electronic circuits. Therefore, integrated and comprehensive training is needed for teachers to utilize software engineering. The training was attended by 15 teachers who taught on productive subjects (Engineering). From the results of this training it appears that all participants can already use NI Multisim and Proteus software. Based on the questionnaire indicators that have been analyzed it can also be seen that most of the participants are of the view that the implementation of the training has provided profound benefits and is very helpful in improving the participants' quality